ANTI-INFLAMMATORY ACTIVITY OF TRAUMEEL (A HOMEOPATHIC PREPARATION) IN EXPERIMENTAL ANIMALS-RATS - Kumar, N. Raveendra; Kumar, N. Siva; B Gangadhar, Parabattula (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: To evaluate the anti-inflammatory effect of traumeel on acute and chronic inflammatory experimental animal models (rats). Methods: The traumeel, a homeo medicinal preparation was tested for its efficacy in acute and chronic inflammatory rats. In acute models: Rat paw edema method was used. In this model, rats were divided into four groups, six rats each. Group-I (NC), received 2% GA 2 ml, Group-II (PC) received aspirin (200 mg/kg), Group-III, intravenous received low dose (6CH) and high dose (300CH) of traumeel, preparation orally. Edema was developed in injected paw. Immediately the foot edema volume was measured at 0 hr and at the end of 3rd hr with a plethysmograph. The percentage of inhibition of edema by drugs was measured and compared between the test, control and standard groups. In chronic models: Granuloma method was used, and test drugs were given for 7 days. The animals were divided and treated same as in the acute model. After 7 days treatment, on 8th day animals were sacrificed each implanted pellet was extracted with adherent granulation tissue. These pellets were dried and weighed. The known weight was deducted from granulation tissue weight. The mean weight of granulation tissue and difference in weight of granulation tissue for each group was calculated, and the percentage of inhibition of inflammation was calculated. Results: The percentage of inhibition of edema in the acute model with 6CH, 300CH after 3 hrs is 51%, 76% respectively and with aspirin is 79%. In chronic models, the percentage of inhibition of granulation tissue with 6CH, 300CH after 7 days is 19.5%, 32.85%, respectively and with aspirin is 41.95%. The reduction of inflammation was statistically significant in each group is (p<0.001). Conclusion: Traumeel, a homeo preparation is a best alternative drug for the treatment of acute inflammatory conditions with no side effects. Keywords: Inflammation, Traumeel preparation, Carrageenan, Aspirin. Â 